2022
DOI: 10.1039/d2sc04344k
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-controlled C–H or C–C alkynylation of cyclopropanes: generation of aryl radical cations by direct light activation of hypervalent iodine reagents

Abstract: We report the first oxidative C-H alkynylation of arylcyclopropanes. Irradiation of ethynylbenziodoxolone (EBX) reagents with visible light at 440 nm promoted the reaction. By the choice of the aryl group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Building upon this work, our group recently developed a substrate-controlled C-H alkynylation or C-C oxyalkynylation of aryl cyclopropanes via the direct photoexcitation of Ar-EBX reagents (Scheme 41). 149 When the aryl on the cyclopropane was bearing two ortho substituents, an unusual CH-alkynylation was taking place presumably via radical cation I (A). From this intermediate, computations suggested that the conformational constrains induced by the aryl ring favored H-abstraction followed by alkynylation over ring opening.…”
Section: Direct Photo-excitation Of Ar-ebx Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon this work, our group recently developed a substrate-controlled C-H alkynylation or C-C oxyalkynylation of aryl cyclopropanes via the direct photoexcitation of Ar-EBX reagents (Scheme 41). 149 When the aryl on the cyclopropane was bearing two ortho substituents, an unusual CH-alkynylation was taking place presumably via radical cation I (A). From this intermediate, computations suggested that the conformational constrains induced by the aryl ring favored H-abstraction followed by alkynylation over ring opening.…”
Section: Direct Photo-excitation Of Ar-ebx Reagentsmentioning
confidence: 99%
“…Building upon this work, our group recently developed a substrate-controlled C–H alkynylation or C–C oxyalkynylation of aryl cyclopropanes via the direct photoexcitation of Ar-EBX reagents ( Scheme 41 ). 149 …”
Section: Radical-based Alkynylation Reactionsmentioning
confidence: 99%
“…Recently, Waser and coworkers extended the repertoire of reactions based on direct excitation of EBX to C–H alkynylation of arylcyclopropanes (Scheme 10B). 52 The substituion of the aryl group was found to have an important effect on the reaction outcome. Different ortho substituents steer the reaction towards C–H alkynylation, and in the absence of ortho substituents oxyalkynylation of the C–C bond prevails.…”
Section: Reaction Of Benziodoxol Derivativesmentioning
confidence: 99%
“…10 Recently, Waser et al disclosed that the hypervalent alkynyl iodine reagent itself acted as an efficient photocatalyst, and an external-photocatalyst-free reaction was elegantly developed. 11 Despite these advancements, to the best of our knowledge, the formation of benzylic C(sp 3 )–C(sp 3 ) bonds by ring-opening functionalization of aryl cyclopropanes has not been reported except for a previous report on gem -difluoro substituted aryl cyclopropanes. 12 As a consequence, we speculated that in the presence of a radical allylation reagent such as allyl sulphone 13 and an external nucleophile, a ring-opening 1,3-allylfunctionalization might be realized in a redox-neutral and regioselective manner.…”
Section: Introductionmentioning
confidence: 99%